Noncontact, nondestructive evaluation of realistic cracks with surface acoustic waves by scanning excitation and detection lasers - Hess, Peter; Lomonosov, Alexey M. (International journal of thermophysics, 2013)
Nondestructive evaluation of surface-breaking cracks with a scanning laser source, a scanning laser probe, or a scanning laser pump-probe setup is discussed. Multimode scattering of laser-excited surface acoustic wave pulses by artificial slots, realistic fatigue, or impulsive cracks is considered. This includes measuring the size of cracks in the micrometer-to-millimeter range by optical recording of the complete displacement or velocity field around the crack. Results obtained with a scanning pump-probe setup for a partially closed microcrack, generated by an elastic shock pulse in silica, are compared with those achieved with a scanning source or scanning probe for machined open notches. Crack size analysis based on the frequency spectrum of the reflected Rayleigh wave and the time lag of the transmitted Rayleigh wave is discussed. Signal enhancement effects observed in the displacement and velocity field near the crack are studied.
Gesehen am 07.05.2021